1983
DOI: 10.1111/j.1365-3180.1983.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions and isozyme polymorphism in Chenopodium album L.

Abstract: Electrophoretic variations within four enzyme systems (a-esterase, acid phosphatase, malate dehydrogenase and leucine amino peptidase), were studied for various garden and field populations of Chenopodium album. A correlation was found between the degree of polymorphism for the electrophoretic traits and environmental conditions. The amount of phenotypic polymorphism is very high in gardens, intermediate in an untreated and, low in herbicide-treated fields and nil for a triazine resistant population in a maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…The same results have been found for predominantly autogamous triazine-resistant weeds, such as Amaranthus retroflexus (Warwick & Black, 1986). Within an allogamous species, Chenopodium album, it has been shown by Al Mouemar & Gasquez (1983) that the rate of phenotypic polymorphism is very high in gardens, reduced in treated fields and reduced to only one phenotype in the triazine-resistant populations. Recent results have shown that within an allogamous weed (Brassica rapa), the triazine-resistant populations have only a slightly reduced genetic variability (Warwick & Black, 1993 (Chauvel, 1991).…”
Section: +____+____+___-+----+----+----+-----+----+----±supporting
confidence: 72%
See 1 more Smart Citation
“…The same results have been found for predominantly autogamous triazine-resistant weeds, such as Amaranthus retroflexus (Warwick & Black, 1986). Within an allogamous species, Chenopodium album, it has been shown by Al Mouemar & Gasquez (1983) that the rate of phenotypic polymorphism is very high in gardens, reduced in treated fields and reduced to only one phenotype in the triazine-resistant populations. Recent results have shown that within an allogamous weed (Brassica rapa), the triazine-resistant populations have only a slightly reduced genetic variability (Warwick & Black, 1993 (Chauvel, 1991).…”
Section: +____+____+___-+----+----+----+-----+----+----±supporting
confidence: 72%
“…For example, selection for triazine resistance can lead to a significant decrease in polymorphism (Al Mouemar & Gasquez, 1983;Warwick & Black, 1986). Similar results have been found within resistant insect populations (Georghiou, 1990).…”
Section: Atopecurus Myosuroides Hudson (Black-grass or Slender Foxtaisupporting
confidence: 71%
“…The effect of environmental factors on morpho-agronomic characteristics was estimated by Pearson's correlation using SPSS for Windows 14. Patterns or zymograms were produced on the basis of numbers and of relative position of bands (Mouemer and Gasquez 1983) and the variable types (in respect of number and position of bands) were considered as different patterns in the zymogram.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic polymorphism for each enzyme and plant lot was estimated using the Pi index utilized by Kahler et al . (1980), Al Mouemar & Gasquez (1983) and Warwick & Black (1986) :…”
Section: Methodsmentioning
confidence: 99%